THE INFLUENCE OF WORK-LIFE BALANCE, WORK ENVIRONMENT, AND WORK STRESS ON EMPLOYEE PERFORMANCE WITH RESILIENCE AS A MEDIATING VARIABLE IN THE MILLENNIAL GENERATION - Salendra, Tania (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the influence of work-life balance, work environment, and work stress on the performance of millennial employees with resilience as a mediating variable. This issue is relevant in the context of increasing challenges in achieving work-life balance and work-related stress among young people. Using an explanatory quantitative approach, data were collected from 400 respondents through purposive sampling and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that work-life balance and work stress have a direct, positive, and significant influence on performance, as does resilience. Meanwhile, the work environment has a direct negative influence on performance but enhances resilience, which positively impacts performance. Resilience was found to be a significant mediator in the relationship between work stress and performance, as well as between the work environment and performance, but it was not significant in mediating the influence of work-life balance on performance. These findings highlight the importance of work conditions and psychological capacity in influencing employee productivity, as well as reinforcing the relevance of expectancy theory in explaining performance motivation. Further research is recommended to include cross-generational samples and longitudinal designs to evaluate the stability of relationships between variables over time.